Effect analysis of repeated transcranial magnetic stimulation combined with fluoxetine in the treatment of first-episode adolescent depression - Jiao, Long; Chen, Tingting; Huang, Yuanyuan; Huang, Xiaoqin (Frontiers in Psychiatry, 2024)
Objectives This study aims to evaluate the efficacy of repeated transcranial magnetic stimulation (rTMS) combined with fluoxetine in enhancing the early antidepressant response in first-episode adolescent depression cases, providing insights for patient diagnosis and treatment. Methods One hundred and thirty-five adolescents experiencing their first depressive episode were randomly assigned to either a sham group treated with fluoxetine or to low or high repetitive transcranial magnetic stimulation (rTMS) groups receiving both rTMS and fluoxetine. Therapeutic effects were assessed by comparing changes in Hamilton Depression Scale (HAMD-17) scores, cognitive function scores from the Wisconsin Card Sorting Test (WCST), and Clinical Global Impression-improvement (CGI-I) scores, along with recording adverse reactions. Results The total effectiveness rate in the rTMS groups (Low, 95.56%; High, 97.78%) was significantly higher than in the Sham rTMS group (80%) (F = 11.15, P<0.0001). Post-treatment, not only the Low but also the High rTMS group exhibited more significant reductions in HAMD-17 (Low, 21.05; High, 21.45) and CGI-I scores (Low, 3.44; High, 3.60) compared to the Sham rTMS group (HAMD-17, 16.05; CGI-I, 2.57) (two weeks: F = 7.889, P = 0.0006; four weeks: F = 15.900, P<0.0001). Additionally, the two rTMS groups exhibited fewer erroneous responses and persistent errors in the WCST and completed more WCST categorizations than the Sham rTMS group. There was no significant difference in adverse reaction rates between the groups (F=4.421, P=0.0794). Conclusions The combination of fluoxetine with rTMS demonstrates enhanced therapeutic effectiveness in treating adolescent depression, effectively controlling disease progression, reducing depressive symptoms, and improving cognitive function, making it a valuable clinical approach.